2005
DOI: 10.1111/j.1460-9568.2005.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitability changes in human corticospinal projections to muscles moving hand and fingers while viewing a reaching and grasping action

Abstract: Excitability of the H-reflex in the relaxed flexor digitorum superficialis (FDS) muscle was tested in five subjects observing a reaching and grasping action. The amplitude of the FDS H-reflex was modulated with a peak occurring during the hand-opening phase of the observed movement. When the H-reflex was facilitated by subliminal transcranial magnetic stimulation (TMS), the modulation was larger than for an unconditioned reflex of similar size. This suggests that the primary motor cortex excitability is modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 34 publications
9
86
3
Order By: Relevance
“…This observation is in line with the findings of previous studies (Leocani et al, 2000;Nikolova et al, 2006;Rossini et al, 1988;van den Wildenberg et al, 2010). However, our main interest was in the possible effect of emotional processing on the dynamics of corticospinal excitability and in extending previous results that showed a tonic effect of emotion on the action system.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This observation is in line with the findings of previous studies (Leocani et al, 2000;Nikolova et al, 2006;Rossini et al, 1988;van den Wildenberg et al, 2010). However, our main interest was in the possible effect of emotional processing on the dynamics of corticospinal excitability and in extending previous results that showed a tonic effect of emotion on the action system.…”
Section: Discussionsupporting
confidence: 82%
“…Neutral stimuli mostly depict static objects, whereas pleasant and unpleasant pictures mostly show humans involved in dynamic situations-that is, engaged in some mouth/facial or hand/arm activity or operating an object such as a gun or a knife. Observation of others' (emotionally neutral) actions increases the MEP amplitude (Fadiga, Fogassi, Pavesi, & Rizzolatti, 1995;Montagna, Cerri, Borroni, & Baldissera, 2005), as does observation of implied motion stimuli (Urgesi, Moro, Candidi, & Aglioti, 2006). As a result, the present MEP patterns might also be explained by the difference in action content of the stimuli.…”
Section: Alternative Accountsmentioning
confidence: 83%
See 1 more Smart Citation
“…The aim of this study was to disentangle the relative contribution and combination of different 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 14 person being observed and the observer's ones (Avenanti, Bolognini, Maravita, & Aglioti, 2007;Borroni et al, 2005;Borroni & Baldissera, 2008;Fadiga et al, 1995;Gangitano et al, 2001;Montagna et al, 2005;Strafella & Paus, 2000;Urgesi et al, 2006) and an anticipatory modulation of motor activations according to the final end of the perceived movement. While the video in which the soccer player suddenly stopped after kicking the ball ('still' condition) determined a decrease in CS excitability -signaling a transition to the motor profile designated by the action seen, observing the videos in which the player continued to run extended CS activity until the final phase of the action sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Those investigators considered the effect an expression of a mechanism blocking the overt execution of observed actions. Modulation of motor potentials evoked by TMS during action observation 3,20,21 appears to be specific, then, for the muscles involved in executing an action 3 and follows, in an anticipatory fashion 22 , the same temporal activation pattern 17,23 . Along these lines, Urgesi and colleagues 24,25 recently found that observation of start and middle phases of grasp actions engendered a significantly higher motor facilitation than observing their final postures.…”
Section: Introductionmentioning
confidence: 99%